(untitled) (Al-Farooq Journal of Sciences, 2026)
Background: Chest computed tomography (CT) is essential for the detection and follow-up of pulmonary nodules, but repeated examinations require radiation dose optimization while maintaining diagnostic image quality. The relationship between pulmonary nodule type and CT radiation dose indices remains insufficiently investigated. Objective: To compare CTDIvol and SSDE between chest CT examinations associated with non-calcified solid and part-solid pulmonary nodules while accounting for the correlation among multiple nodules within the same patient. Materials and Methods: A retrospective comparative study included 99 non-calcified pulmonary nodules from 51 patients, comprising 63 solid nodules (63.6%) and 36 part-solid nodules (36.4%). Patient age, nodule type, CTDIvol, and SSDE were recorded. A Generalized Estimating Equations (GEE) model was used with Patient ID as the clustering unit. Statistical significance was set at p < 0.05. Results: Mean age was 57.37 ± 16.90 years for solid nodules and 66.56 ± 14.24 years for part-solid nodules. Mean CTDIvol was 6.06 ± 2.05 mGy and 6.09 ± 1.75 mGy, respectively, while mean SSDE was 7.77 ± 2.34 mGy and 7.52 ± 2.24 mGy, respectively. After accounting for within-patient clustering, no statistically significant differences were observed in age (mean difference: 0.14 years; 95% CI: −0.04 to 0.32; p = 0.117), CTDIvol (0.03 mGy; 95% CI: −0.36 to 0.42; p = 0.891), or SSDE (−0.01 mGy; 95% CI: −0.07 to 0.06; p = 0.874). Conclusion: No statistically significant differences in CTDIvol or SSDE were found between non-calcified solid and part-solid pulmonary nodules after accounting for within-patient correlation. Nodule type was not associated with the radiation dose indices investigated. These findings highlight the importance of accounting for clustered observations and optimizing chest CT protocols to balance radiation dose and diagnostic image quality.